Institution of Property in the Socialist Community - Karosas, Justinas (Problemos, 1974)
An attempt is made in the article to reveal peculiarities of the Marxist social methodology in the solution of the problem of the social property institution. Contents of the property institution is always economical. Therefore socialization of production is a category of economics. It shows mutual dependence of separate production processes and simultaneously objective possibilities of the juridical socialization of production. The author tries to show the methodological baselessness of the efforts to explicate socialist property relations without regard for the economical content and considers them to be the basis of the socialist economic relations.